Ultraviolet-resistant and high-voltage shock-resistant hydrogenated nitrile rubber and preparation method thereof

By combining hydrogenated nitrile rubber with olefin copolymer and adding modified fillers and functional additives, the stability of existing high-voltage shock-resistant materials in high-voltage environments is solved, significantly improving the material's ultraviolet resistance, shock resistance and oxidation resistance, and extending its service life.

CN119823458AActive Publication Date: 2025-04-15GUANGZHOU MEICUN RUBBER TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510034712.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-09
Publication Date
2025-04-15
Estimated Expiration
2045-01-09

AI Technical Summary

Technical Problem

The existing high-voltage shock-resistant materials have poor long-term stability in high-voltage environments, which are prone to dielectric breakdown or aging problems. The heat resistance and chemical resistance of traditional rubber materials are insufficient, making it difficult to meet the needs of industry and power systems.

Method used

By combining hydrogenated nitrile rubber with olefin copolymer, the benzene ring and furan ring structure is introduced, and modified fillers and functional additives, such as benzotriazole light stabilizers, phenolic antioxidants and phosphite antioxidants, the material's ultraviolet resistance, high-voltage shock resistance and antioxidant properties are improved.

Benefits of technology

It significantly improves the material's UV aging resistance, anti-shock performance and anti-oxidation properties, extends the service life of the material, and balances the mechanical strength and electrical insulation properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005235218320000121
    Figure BDA0005235218320000121
  • Figure BDA0005235218320000131
    Figure BDA0005235218320000131
Patent Text Reader

Abstract

The invention relates to ultraviolet-resistant and high-voltage shock-resistant hydrogenated nitrile rubber and a preparation method thereof, and belongs to the technical field of high polymer material synthesis. By compounding the hydrogenated nitrile rubber and the olefin copolymer, benzene ring and furan ring structures are introduced into the olefin copolymer structure, so that the rubber is endowed with excellent ultraviolet aging resistance and electric shock resistance; the modified filler is added to enhance the mechanical strength, insulativity and high pressure resistance of the rubber; and the benzotriazole light stabilizer, the phenolic antioxidant and the phosphite antioxidant are added, so that the ultraviolet resistance and the oxidation resistance of the material are further improved, and the service life of the material is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of polymer material synthesis, and relates to ultraviolet-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber and a preparation method thereof. Background Art

[0002] Hydrogenated nitrile rubber is a high-performance elastomer prepared by selectively hydrogenating double bonds in nitrile rubber. It is widely used in industry, automobile, aerospace and other fields due to its excellent heat resistance, oil resistance and aging resistance. Especially in high-voltage electric shock environments, higher requirements are placed on the material's aging resistance, UV resistance and dielectric properties. Existing high-voltage electric shock resistant materials generally include polyethylene, polyvinyl chloride and EPDM rubber. Although these materials have certain electric shock resistance, they are limited in high temperature resistance, aging resistance and mechanical properties. In addition, traditional rubber materials such as natural rubber and butadiene rubber have poor heat resistance and chemical resistance, and it is difficult to meet the growing needs of industry and power systems.

[0003] The selection of hydrogenated nitrile rubber as the main matrix material is based on its unique molecular structure and excellent performance. While maintaining the advantages of nitrile rubber in oil resistance and wear resistance, hydrogenated nitrile rubber greatly improves the thermal stability and oxidation resistance of the material by hydrogenating the double bonds, enabling it to be used in harsh environments such as high temperature and high pressure for a long time. Compared with EPDM, hydrogenated nitrile has better mechanical properties and chemical resistance; compared with polyethylene materials, it has better elasticity and processing properties. In addition, the molecular structure of hydrogenated nitrile rubber has polar groups, which makes it more compatible with modified fillers and functional additives, thereby further improving the comprehensive performance of the material. By compounding hydrogenated nitrile rubber with modified fillers, olefin copolymers and additives, not only can the material's UV resistance and high voltage electric shock resistance be significantly improved, but also the mechanical strength and electrical insulation properties can be effectively balanced.

[0004] Although various modified materials have been developed for different application scenarios in the prior art, there are still some shortcomings. First, the long-term stability of traditional rubber-based anti-electric shock materials in high-voltage environments is poor, and dielectric breakdown or aging problems are prone to occur, which limits their service life in complex environments. Secondly, additives and fillers are unevenly dispersed in the matrix, which affects the comprehensive performance of the material. Thirdly, some existing high-performance materials are often costly and complex in process, which is not conducive to large-scale industrial production. Therefore, how to develop a new type of hydrogenated nitrile rubber material that is resistant to UV rays, resistant to high-voltage electric shocks, cost-effective and has good processing performance through molecular design of materials, optimized ratio of additives and process improvements is a problem that needs to be solved urgently. Summary of the invention

[0005] The present invention relates to a hydrogenated nitrile rubber resistant to ultraviolet and high voltage electric shock and a preparation method thereof, and belongs to the technical field of polymer material synthesis. The present invention compounds hydrogenated nitrile rubber and olefin copolymer, introduces benzene ring and furan ring structure into the olefin copolymer structure to give the rubber excellent ultraviolet aging resistance and electric shock resistance; adds modified filler to increase the mechanical strength, insulation and high voltage resistance of the rubber; and adds benzotriazole light stabilizer, phenol antioxidant and phosphite antioxidant to further improve the material's ultraviolet resistance and antioxidant performance, thereby extending the material's service life.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A hydrogenated nitrile rubber resistant to ultraviolet and high voltage electric shock comprises the following components by weight: 80-120 parts of hydrogenated nitrile rubber, 5-20 parts of olefin copolymer, 20-50 parts of modified filler, 2-6 parts of crosslinking agent and 0.8-5 parts of functional additive.

[0008] As a preferred technical solution of the present invention, the olefin copolymer component includes 1,3-butadiene, styrene, and furanyl olefin, and the mass ratio of the 1,3-butadiene, styrene, and furanyl olefin is 5-15:20-30:2-8; the preparation method of the olefin copolymer is: under nitrogen protection, the monomers 1,3-butadiene, styrene, and furanyl olefin are dissolved in a solvent toluene, n-butyl lithium is added as an initiator, tetrahydrofuran is used as a co-catalyst, after stirring at 30-80°C for 2-6h, methanol is added to terminate the polymerization reaction, and the olefin copolymer is obtained through precipitation, washing and drying.

[0009] As a preferred technical solution of the present invention, the furanyl olefin is at least one of 2-vinylfuran, 2-furan acrylic acid, 2-furan acrolein, 3-(2-furan) acrolein, and 4-(2-furanyl)-3-butene-2-one.

[0010] As a preferred technical solution of the present invention, the mass ratio of the monomer, toluene, n-butyl lithium and tetrahydrofuran is 1:6-20:0.001-0.01:0.01-0.05.

[0011] As a preferred technical solution of the present invention, the modified filler includes modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth. The preparation method of the modified filler is: prepare 3-5wt% anhydrous ethanol solution of silane coupling agent, stir for 20-40min, add polyester fiber, quartz sand, limestone and diatomaceous earth, ultrasonically disperse for 20-40min, soak for 1-2h, filter and dry to obtain modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth.

[0012] As a preferred technical solution of the present invention, the quartz sand has a particle size of 0.5-10 μm, the limestone has a particle size of 1-20 μm, and the diatomaceous earth has a particle size of 1-15 μm; the mass ratio of the polyester fiber, quartz sand, limestone and diatomaceous earth is 1-2:2-4:1-3:1-2, and the ratio of the silane coupling agent to the total mass of the polyester fiber, quartz sand, limestone and diatomaceous earth is 1-3:100.

[0013] As a preferred technical solution of the present invention, the cross-linking agent is a peroxide cross-linking agent, a vulcanizing agent and an auxiliary cross-linking agent; the peroxide cross-linking agent is one of di-tert-butyl peroxide and benzoyl peroxide, the vulcanizing agent is at least one of sulfur, N-cyclohexyl-2-benzothiazole sulfenamide, hexamethylenetetramine, and N-tert-butyl-2-benzothiazole sulfenamide, and the auxiliary cross-linking agent is at least one of zinc oxide, stearic acid, tetraisopropylthiuram disulfide, tetraethylthiuram disulfide, and dibenzothiazole disulfide; the mass ratio of the peroxide cross-linking agent, the vulcanizing agent and the auxiliary cross-linking agent is 1-3:0.5-3:0.5-2.

[0014] As a preferred technical solution of the present invention, the functional additives include benzotriazole light stabilizers, phenolic antioxidants and phosphite antioxidants, and the mass ratio of the benzotriazole light stabilizers, phenolic antioxidants and phosphite antioxidants is 0.5-3:0.1-0.5:0.2-1.

[0015] The method for preparing the ultraviolet-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber is characterized in that it comprises the following steps:

[0016] (1) adding olefin copolymer to hydrogenated nitrile rubber, stirring evenly, adding modified filler and crosslinking agent, and kneading at 120-170° C. for 10-20 minutes;

[0017] (2) adding functional additives and melting and mixing at 120-180° C. for 10-20 min;

[0018] (3) The mixture is extruded and granulated.

[0019] Beneficial effects of the present invention:

[0020] (1) The present invention introduces benzene ring and furan ring structures into the structure of the olefin copolymer by compounding hydrogenated nitrile rubber and olefin copolymer. The benzene ring and furan ring are conjugated ring structures with strong rigidity, have high chemical stability and intramolecular energy shielding effect, so that the overall dielectric constant of the material is improved, and the dielectric loss under the electric field is reduced, which can effectively slow down the concentration of the local electric field inside the material under high voltage, thereby delaying the occurrence of electrical breakdown. In addition, the rigid regions of the benzene ring and furan ring can form a physical barrier under high voltage electric shock, hinder the expansion of electric trees caused by local discharge, reduce the formation of breakdown paths, and improve the breakdown voltage resistance of the material.

[0021] (2) The present invention increases the mechanical strength, insulation and high voltage resistance of rubber by adding modified fillers. The modified polyester fiber has high tensile strength and rigidity, and forms a mesh or reinforced skeleton structure in the matrix, which can effectively absorb the energy caused by external impact or electric shock, reduce local stress concentration, and thus improve the material's resistance to electric shock and cracking performance; the dielectric constant of quartz sand is low, which can reduce the dielectric loss of the material, inhibit the expansion of electric tree in the high-voltage electric field, and significantly improve the breakdown voltage of the composite material. In addition, quartz sand has high reflectivity and transmittance to ultraviolet rays, which can effectively shield a part of ultraviolet light energy and reduce its destructive effect on the matrix; limestone is a high resistivity material, which can effectively improve the insulation performance of the composite material, reduce the conductivity and breakdown risk in the high electric field environment, and the scattering effect on ultraviolet light can reduce the amount of ultraviolet light absorbed by the matrix material and slow down the photo-oxidation degradation process; the low dielectric constant and high resistivity of diatomaceous earth make it have good insulation in a high-voltage environment, and can effectively inhibit the conductivity behavior and dielectric breakdown under the high-voltage electric field.

[0022] (3) Benzo-based light stabilizers (such as benzotriazole or benzophenone) contain conjugated aromatic ring structures that can effectively absorb ultraviolet energy in the wavelength range of 200-400nm, avoiding the direct absorption of ultraviolet photon energy by the molecular bonds of the matrix material, thereby preventing chemical bond breakage and molecular chain degradation; phenolic antioxidants are powerful free radical scavengers that inhibit the oxidative degradation of materials mainly by capturing free radicals and terminating free radical chain reactions; phosphite antioxidants are multifunctional antioxidants that enhance antioxidant properties mainly by decomposing peroxides and protecting other antioxidants in the material (such as phenols); the three additives construct a multi-level protection system from ultraviolet light shielding, free radical capture to peroxide decomposition, effectively improving the material's UV resistance and antioxidant properties and delaying the degradation process. DETAILED DESCRIPTION

[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.

[0024] In the following examples and comparative examples, the hydrogenated nitrile rubber was purchased from Shanghai Jiader Chemical Technology Co., Ltd.; polyester fiber was purchased from Taicheng Fiber Co., Ltd.; quartz sand was purchased from Hengyang Mineral Products Processing Plant with the item number 012; limestone was purchased from Huaian Dingsheng Calcium Industry Co., Ltd.; diatomaceous earth was purchased from Shuntian Mineral Products Processing Plant with the item number S95621; benzotriazole light stabilizer was purchased from Huichen Chemical Co., Ltd. with the item number UV-326; phenolic antioxidant was purchased from Jiangsu Ruicheng Biotechnology Co., Ltd. with the item number 25013 and phosphite antioxidant was purchased from Benock Biotechnology Co., Ltd.; silane coupling agent was purchased from Shandong Bosheng Chemical Co., Ltd.; the single product number is KH570.

[0025] Example 1

[0026] A hydrogenated nitrile rubber resistant to ultraviolet and high voltage electric shock comprises the following components in parts by weight: 100 parts of hydrogenated nitrile rubber, 15 parts of olefin copolymer, 35 parts of modified filler, 4 parts of crosslinking agent and 3 parts of functional additive.

[0027] The olefin copolymer components include 1,3-butadiene, styrene, and furanyl olefin, and the mass ratio of the 1,3-butadiene, styrene, and furanyl olefin is 10:25:5; the preparation method of the olefin copolymer is: under nitrogen protection, the monomers 1,3-butadiene, styrene, and furanyl olefin are dissolved in a solvent toluene, n-butyl lithium is added as an initiator, tetrahydrofuran is added as a co-catalyst, after stirring at 55° C. for 4 hours, methanol is added to terminate the polymerization reaction, and the olefin copolymer is obtained through precipitation, washing, and drying.

[0028] The furanyl olefin is 2-vinylfuran.

[0029] The mass ratio of the monomer, toluene, n-butyl lithium and tetrahydrofuran is 1:13:0.005:0.03.

[0030] The modified filler comprises modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth. The preparation method of the modified filler comprises: preparing a 4wt% silane coupling agent anhydrous ethanol solution, stirring for 30 minutes, adding polyester fiber, quartz sand, limestone and diatomaceous earth, ultrasonically dispersing for 30 minutes, and then soaking for 1.5 hours, filtering and drying to obtain modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth.

[0031] The quartz sand has a particle size of 5 μm, the limestone has a particle size of 10 μm, and the diatomaceous earth has a particle size of 10 μm; the mass ratio of the polyester fiber, quartz sand, limestone and diatomaceous earth is 1.5:3:2:1.5, and the ratio of the silane coupling agent to the total mass of the polyester fiber, quartz sand, limestone and diatomaceous earth is 2:100.

[0032] The crosslinking agent is a peroxide crosslinking agent, a vulcanizing agent and an auxiliary crosslinking agent; the peroxide crosslinking agent is di-tert-butyl peroxide, the vulcanizing agent is sulfur, and the auxiliary crosslinking agent is zinc oxide; the mass ratio of the peroxide crosslinking agent, the vulcanizing agent and the auxiliary crosslinking agent is 2:2:1.

[0033] The functional additives include a benzotriazole light stabilizer, a phenolic antioxidant and a phosphite antioxidant, and the mass ratio of the benzotriazole light stabilizer, the phenolic antioxidant and the phosphite antioxidant is 2:0.3:0.6.

[0034] The method for preparing the ultraviolet-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber comprises the following steps:

[0035] (1) Adding olefin copolymer to hydrogenated nitrile rubber, stirring evenly, adding modified filler and crosslinking agent, and kneading at 150° C. for 15 minutes;

[0036] (2) adding functional additives and melt mixing at 150°C for 15 minutes;

[0037] (3) The mixture is extruded and granulated.

[0038] Example 2

[0039] A hydrogenated nitrile rubber resistant to ultraviolet and high voltage electric shock comprises the following components by weight: 80 parts of hydrogenated nitrile rubber, 5 parts of olefin copolymer, 20 parts of modified filler, 2 parts of crosslinking agent and 0.8 parts of functional additive.

[0040] The olefin copolymer components include 1,3-butadiene, styrene, and furanyl olefin, and the mass ratio of the 1,3-butadiene, styrene, and furanyl olefin is 5:20:2; the preparation method of the olefin copolymer is: under nitrogen protection, the monomers 1,3-butadiene, styrene, and furanyl olefin are dissolved in a solvent toluene, n-butyl lithium is added as an initiator, tetrahydrofuran is added as a co-catalyst, after stirring at 30° C. for 6 hours, methanol is added to terminate the polymerization reaction, and the olefin copolymer is obtained through precipitation, washing, and drying.

[0041] The furanyl olefin is 2-furanacrylic acid.

[0042] The mass ratio of the monomer, toluene, n-butyl lithium and tetrahydrofuran is 1:6:0.001:0.01.

[0043] The modified filler comprises modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth. The preparation method of the modified filler comprises: preparing a 3wt% anhydrous ethanol solution of silane coupling agent, stirring for 20 minutes, adding polyester fiber, quartz sand, limestone and diatomaceous earth, ultrasonically dispersing for 20 minutes, and then soaking for 1 hour, filtering and drying to obtain modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth.

[0044] The particle size of the quartz sand is 5 μm, the particle size of the limestone is 10 μm, and the particle size of the diatomaceous earth is 10 μm; the mass ratio of the polyester fiber, quartz sand, limestone and diatomaceous earth is 1:2:1:1, and the ratio of the silane coupling agent to the total mass of the polyester fiber, quartz sand, limestone and diatomaceous earth is 1:100.

[0045] The crosslinking agent is a peroxide crosslinking agent, a vulcanizing agent and an auxiliary crosslinking agent; the peroxide crosslinking agent is di-tert-butyl peroxide, the vulcanizing agent is N-cyclohexyl-2-benzothiazole sulfonamide, and the auxiliary crosslinking agent is stearic acid; the mass ratio of the peroxide crosslinking agent, the vulcanizing agent and the auxiliary crosslinking agent is 1:0.5:0.5.

[0046] The functional additives include a benzotriazole light stabilizer, a phenolic antioxidant and a phosphite antioxidant, and the mass ratio of the benzotriazole light stabilizer, the phenolic antioxidant and the phosphite antioxidant is 0.5:0.1:0.2.

[0047] The method for preparing the ultraviolet-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber comprises the following steps:

[0048] (1) Adding olefin copolymer to hydrogenated nitrile rubber, stirring evenly, adding modified filler and crosslinking agent, and kneading at 120° C. for 20 minutes;

[0049] (2) adding functional additives and melting and mixing at 120°C for 20 minutes;

[0050] (3) The mixture is extruded and granulated.

[0051] Example 3

[0052] A hydrogenated nitrile rubber resistant to ultraviolet and high voltage electric shock comprises the following components in parts by weight: 120 parts of hydrogenated nitrile rubber, 20 parts of olefin copolymer, 50 parts of modified filler, 6 parts of crosslinking agent and 5 parts of functional additive.

[0053] The olefin copolymer components include 1,3-butadiene, styrene, and furanyl olefin, and the mass ratio of the 1,3-butadiene, styrene, and furanyl olefin is 15:30:8. The preparation method of the olefin copolymer is as follows: under nitrogen protection, the monomers 1,3-butadiene, styrene, and furanyl olefin are dissolved in a solvent toluene, n-butyl lithium is added as an initiator, tetrahydrofuran is added as a co-catalyst, and after stirring at 80° C. for 6 hours, methanol is added to terminate the polymerization reaction, and the olefin copolymer is obtained through precipitation, washing, and drying.

[0054] The furanyl olefin is 2-furanacrolein.

[0055] The mass ratio of the monomer, toluene, n-butyl lithium and tetrahydrofuran is 1:20:0.01:0.05.

[0056] The modified filler comprises modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth. The preparation method of the modified filler comprises: preparing a 5wt% silane coupling agent anhydrous ethanol solution, stirring for 40 minutes, adding polyester fiber, quartz sand, limestone and diatomaceous earth, ultrasonically dispersing for 40 minutes, and then soaking for 2 hours, filtering and drying to obtain modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth.

[0057] The quartz sand has a particle size of 5 μm, the limestone has a particle size of 10 μm, and the diatomaceous earth has a particle size of 10 μm; the mass ratio of the polyester fiber, quartz sand, limestone and diatomaceous earth is 1-2:2-4:1-3:1-2, and the ratio of the silane coupling agent to the total mass of the polyester fiber, quartz sand, limestone and diatomaceous earth is 3:100.

[0058] The crosslinking agent is a peroxide crosslinking agent, a vulcanizing agent and an auxiliary crosslinking agent; the peroxide crosslinking agent is di-tert-butyl peroxide, the vulcanizing agent is hexamethylenetetramine, and the auxiliary crosslinking agent is tetraisopropylthiuram disulfide; the mass ratio of the peroxide crosslinking agent, the vulcanizing agent and the auxiliary crosslinking agent is 3:3:2.

[0059] The functional additives include a benzotriazole light stabilizer, a phenolic antioxidant and a phosphite antioxidant, and the mass ratio of the benzotriazole light stabilizer, the phenolic antioxidant and the phosphite antioxidant is 3:0.5:1.

[0060] The method for preparing the ultraviolet-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber comprises the following steps:

[0061] (1) Adding olefin copolymer to hydrogenated nitrile rubber, stirring evenly, adding modified filler and crosslinking agent, and kneading at 170° C. for 10 minutes;

[0062] (2) adding functional additives and melting and mixing at 180°C for 20 minutes;

[0063] (3) The mixture is extruded and granulated.

[0064] Example 4

[0065] A hydrogenated nitrile rubber resistant to ultraviolet and high voltage electric shock comprises the following components in parts by weight: 110 parts of hydrogenated nitrile rubber, 10 parts of olefin copolymer, 50 parts of modified filler, 3 parts of crosslinking agent and 4 parts of functional additive.

[0066] The olefin copolymer components include 1,3-butadiene, styrene, and furanyl olefin, and the mass ratio of the 1,3-butadiene, styrene, and furanyl olefin is 10:20:8; the preparation method of the olefin copolymer is: under nitrogen protection, the monomers 1,3-butadiene, styrene, and furanyl olefin are dissolved in a solvent toluene, n-butyl lithium is added as an initiator, tetrahydrofuran is added as a co-catalyst, after stirring at 40° C. for 4 hours, methanol is added to terminate the polymerization reaction, and the olefin copolymer is obtained through precipitation, washing, and drying.

[0067] The furanyl olefin is 3-(2-furan)acrolein.

[0068] The mass ratio of the monomer, toluene, n-butyl lithium and tetrahydrofuran is 1:20:0.001:0.01.

[0069] The modified filler comprises modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth. The preparation method of the modified filler comprises: preparing a 4wt% silane coupling agent anhydrous ethanol solution, stirring for 25 minutes, adding polyester fiber, quartz sand, limestone and diatomaceous earth, ultrasonically dispersing for 25 minutes, and then soaking for 1 hour, filtering and drying to obtain modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth.

[0070] The quartz sand has a particle size of 5 μm, the limestone has a particle size of 10 μm, and the diatomaceous earth has a particle size of 10 μm; the mass ratio of the polyester fiber, quartz sand, limestone and diatomaceous earth is 1-2:2-4:1-3:1-2, and the ratio of the silane coupling agent to the total mass of the polyester fiber, quartz sand, limestone and diatomaceous earth is 1:100.

[0071] The crosslinking agent is a peroxide crosslinking agent, a vulcanizing agent and an auxiliary crosslinking agent; the peroxide crosslinking agent is benzoyl peroxide, the vulcanizing agent is N-tert-butyl-2-benzothiazole sulfenamide, and the auxiliary crosslinking agent is tetraethylthiuram disulfide; the mass ratio of the peroxide crosslinking agent, the vulcanizing agent and the auxiliary crosslinking agent is 1:3:0.5.

[0072] The functional additives include a benzotriazole light stabilizer, a phenolic antioxidant and a phosphite antioxidant, and the mass ratio of the benzotriazole light stabilizer, the phenolic antioxidant and the phosphite antioxidant is 0.5:0.5:1.

[0073] The method for preparing the ultraviolet-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber comprises the following steps:

[0074] (1) Adding olefin copolymer to hydrogenated nitrile rubber, stirring evenly, adding modified filler and crosslinking agent, and kneading at 140° C. for 14 minutes;

[0075] (2) adding functional additives and melting and mixing at 140°C for 10 min;

[0076] (3) The mixture is extruded and granulated.

[0077] Comparative Example 1

[0078] On the basis of Example 1, no olefin copolymer is added, the amount of hydrogenated nitrile rubber added is changed to 115 parts, and the rest is consistent with Example 1.

[0079] Comparative Example 2

[0080] On the basis of Example 1, polyester fiber is not added to the modified filler, the mass ratio of quartz sand, limestone and diatomaceous earth is changed to 4.5:2:1.5, and the rest is consistent with Example 1.

[0081] Comparative Example 3

[0082] On the basis of Example 1, quartz sand was not added to the modified filler, the mass ratio of polyester fiber, limestone and diatomaceous earth was changed to 1.5:5:1.5, and the rest was consistent with Example 1.

[0083] Comparative Example 4

[0084] On the basis of Example 1, no limestone is added to the modified filler, the mass ratio of polyester fiber, quartz sand and diatomaceous earth is changed to 1.5:3:3.5, and the rest is consistent with Example 1.

[0085] Comparative Example 5

[0086] On the basis of Example 1, diatomaceous earth was not added to the modified filler, the mass ratio of polyester fiber, quartz sand and limestone was changed to 3:3:2, and the rest was consistent with Example 1.

[0087] Comparative Example 6

[0088] On the basis of Example 1, no benzotriazole light stabilizer is added as the functional additive, the mass ratio of phenolic antioxidant to phosphite antioxidant is changed to 2.3:0.6, and the rest is consistent with Example 1.

[0089] Comparative Example 7

[0090] On the basis of Example 1, no phenolic antioxidant is added as the functional additive, the mass ratio of the benzotriazole light stabilizer to the phosphite antioxidant is changed to 2:0.9, and the rest is consistent with Example 1.

[0091] Comparative Example 8

[0092] On the basis of Example 1, no phosphite antioxidant is added as the functional additive, the mass ratio of the benzotriazole light stabilizer and the phenolic antioxidant is changed to 2.6:0.3, and the rest is consistent with Example 1.

[0093] Performance Test:

[0094] Anti-ultraviolet aging test: According to GB / T 528-2009 standard, tensile strength and elongation at break were tested using UVB313 ultraviolet lamp with an irradiance of 0.58W / cm 2 , power is 40W, temperature is 60℃, relative humidity is 60%, after aging time is 500h, tensile strength and elongation at break are measured again;

[0095] The calculation formulas for tensile strength retention and elongation at break retention are as follows:

[0096] Tensile strength retention rate (%) = tensile strength after aging / tensile strength before aging × 100%

[0097] Retention rate of elongation at break (%) = elongation at break after aging / elongation at break before aging × 100%;

[0098] High voltage electric shock resistance test: The breakdown strength test is carried out according to the standard ASTM D149, and the unit is KV / mm.

[0099]

[0100]

[0101] It can be seen from the test results that the present invention enhances the rubber's resistance to ultraviolet aging and electric shock by introducing benzene rings and furan ring structures into the olefin copolymer structure and adding modified fillers; and further improves the material's anti-ultraviolet performance by adding benzotriazole light stabilizers, phenolic antioxidants and phosphite antioxidants.

[0102] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any indirect modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A hydrogenated nitrile rubber resistant to ultraviolet and high voltage shock, characterized in that: The invention comprises the following components in parts by weight: 80-120 parts of hydrogenated nitrile rubber, 5-20 parts of olefin copolymer, 20-50 parts of modified filler, 2-6 parts of crosslinking agent and 0.8-5 parts of functional additive.

2. The UV-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber according to claim 1, characterized in that: The olefin copolymer components include 1,3-butadiene, styrene, and furanyl olefin, and the mass ratio of the 1,3-butadiene, styrene, and furanyl olefin is 5-15:20-30:2-8; the preparation method of the olefin copolymer is: under nitrogen protection, the monomers 1,3-butadiene, styrene, and furanyl olefin are dissolved in a solvent toluene, n-butyl lithium is added as an initiator, tetrahydrofuran is used as a co-catalyst, after stirring at 30-80° C. for 2-6 hours, methanol is added to terminate the polymerization reaction, and the olefin copolymer is obtained through precipitation, washing, and drying.

3. The UV-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber according to claim 2, characterized in that: The furanyl olefin is at least one of 2-vinylfuran, 2-furan acrylic acid, 2-furan acrolein, 3-(2-furan) acrolein, and 4-(2-furanyl)-3-butene-2-one.

4. The UV-resistant and high-voltage shock-resistant hydrogenated nitrile rubber according to claim 2, characterized in that: The mass ratio of the monomer, toluene, n-butyl lithium and tetrahydrofuran is 1:6-20:0.001-0.01:0.01-0.

05.

5. The UV-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber according to claim 1, characterized in that: The modified filler comprises modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth. The preparation method of the modified filler comprises: preparing a 3-5wt% anhydrous ethanol solution of a silane coupling agent, stirring for 20-40 minutes, adding polyester fiber, quartz sand, limestone and diatomaceous earth, ultrasonically dispersing for 20-40 minutes, and then soaking for 1-2 hours, filtering and drying to obtain modified polyester fiber, modified quartz sand, modified limestone and modified diatomaceous earth.

6. The ultraviolet-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber according to claim 5, characterized in that: The particle size of the quartz sand is 0.5-10 μm, the particle size of the limestone is 1-20 μm, and the particle size of the diatomaceous earth is 1-15 μm; the mass ratio of the polyester fiber, quartz sand, limestone and diatomaceous earth is 1-2:2-4:1-3:1-2, and the ratio of the silane coupling agent to the total mass of the polyester fiber, quartz sand, limestone and diatomaceous earth is 1-3:

100.

7. The ultraviolet-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber according to claim 1, characterized in that: The crosslinking agent is a peroxide crosslinking agent, a vulcanizing agent and an auxiliary crosslinking agent; the peroxide crosslinking agent is one of di-tert-butyl peroxide and benzoyl peroxide, the vulcanizing agent is at least one of sulfur, N-cyclohexyl-2-benzothiazole sulfenamide, hexamethylenetetramine, and N-tert-butyl-2-benzothiazole sulfenamide, and the auxiliary crosslinking agent is at least one of zinc oxide, stearic acid, tetraisopropylthiuram disulfide, tetraethylthiuram disulfide, and dibenzothiazole disulfide; the mass ratio of the peroxide crosslinking agent, the vulcanizing agent, and the auxiliary crosslinking agent is 1-3:0.5-3:0.5-2.

8. The UV-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber according to claim 1, characterized in that: The functional additives include benzotriazole light stabilizers, phenolic antioxidants and phosphite antioxidants, and the mass ratio of the benzotriazole light stabilizers, phenolic antioxidants and phosphite antioxidants is 0.5-3:0.1-0.5:0.2-1.

9. A method for preparing a UV-resistant and high-voltage electric shock-resistant hydrogenated nitrile rubber as claimed in any one of claims 1 to 8, characterized in that: The following steps are involved: (1) adding olefin copolymer to hydrogenated nitrile rubber, stirring evenly, adding modified filler and crosslinking agent, and kneading at 120-170° C. for 10-20 minutes; (2) adding functional additives and melting and mixing at 120-180° C. for 10-20 min; (3) Extruding the mixture into granules.

Citation Information

Patent Citations

  • Oil-resistant sealing glue

    CN106634700A

  • Insulation novel material

    CN109265768A

  • High-performance rubber material and preparation method thereof

    CN112745545A

  • Nitrile rubbers

    GB1040993A

  • Rubber composition and rubber seal prepared therewith

    JP2017122140A